The Effect of Story Map Method on Reading Comprehension Ability of the Second-Year Students of SMP Negeri 17 Pekanbaru - Amalia, Salshabhila Putri; Eliwarti, Eliwarti; Syarfi, M (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine the effect of Story Map Method on reading comprehension ability of the second-grade students of SMP Negeri 17 Pekanbaru in the 2024/2025 academic year. The lack of interesting and interactive methods is one of the factors that make students' reading comprehension, especially in narrative texts, difficult to achieve. Story map is one of the interesting and interactive teaching methods because it involves students in learning visually and kinaesthetically. The type of this study is a quasi-experiment, and the design of this study is Non-equivalent Control Group Design. The population of this study was all grade VIII students of SMP Negeri 17 Pekanbaru in the 2024/2025 academic year and consists of 5 classes. The Sampling in this study used purposive random sampling technique by selecting two classes, namely class VIII.2 as the experimental class and VIII.3 as the control class. The data collection instruments in this study were reading comprehension test in the form of narrative text test with multiple choice design. Data collection techniques were done by test techniques. The data analysis technique used is descriptive analysis. Based on the results of data analysis, the value of Sig. (2-tailed) , with = 0.05 and Sig. (2-tailed) = 0.000 (0.000 0.005). It means that H0 is rejected and Ha is accepted, meaning that there is a difference in the average reading comprehension ability of students in the experimental and control class. So, it can be concluded that there a significant effect of the Story Map Method on reading comprehension ability of the second-year students of SMP Negeri 17 Pekanbaru.